Racial Differences in Location Before Hospice Enrollment and Association with Hospice Length of Stay - Johnson, Kimberly S. (2011)
African Americans are less likely than Whites to enroll in hospice. In addition, patients are often referred to hospice very close to death, when they may not have time to take advantage of the full range of hospice services. Understanding how race and location before hospice enrollment are related to hospice length of stay (LOS) may inform the development of interventions to increase timely access to hospice care. Using data from a national hospice provider, African Americans and Whites admitted to routine home hospice care in a private residence between January 1, 2000, and December 31, 2003, were identified. Logistic regression was used to examine the association between race and hospice preadmission location (hospital vs other locations) and preadmission location and hospice LOS (≤7 days vs >7 days) after adjusting for demographic and hospice use variables. Of 43,869 enrollees, 15.3% were African American. One to 2 days before hospice enrollment, African Americans were more likely than Whites to be in the hospital than in all other locations (48.6% vs 32.3%, P < .001; adjusted odds ratio = 1.83, 95% confidence interval = 1.73– 1.95). Regardless of race, those whose preadmission location was the hospital were more likely than those from other locations to die 7 days or less after hospice enrollment. Initiatives to improve end-of-life care should focus on increasing timely access to hospice referrals in settings outside of the hospital. Future research should examine whether racial differences in hospice preadmission location reflect differences in preferences for care or disparities in timely access to hospice referrals in non-acute care settings.